TREX2 enables efficient genome disruption mediated by paired CRISPR-Cas9 nickases that generate 3'-overhanging ends - Yue Wang; Yi-Li Feng; Qian Liu; Jing-Jing Xiao; Si-Cheng Liu; Zhi-Cheng Huang; An-Yong Xie (Elsevier, 2023)
Paired SpCas9 nickases (SpCas9n) are an effective strategy to reduce off-target effect in genome editing. However, this approach is not efficient with 3'-overhanging ends, limiting its applications. In order to expand the utility of paired SpCas9n in genome editing, we tested the effect of the TREX2 3'-5' exonuclease on repair of 3'-overhanging ends. We found ectopic overexpression of Trex2 stimulates the efficiency of paired SpCas9n in genome disruption with 3'-overhanging ends up to 400-fold with little stimulation of off-target editing. TREX2 overexpressed preferentially deletes entire 3' overhangs but has no significant effect on 5' overhangs. Trex2 overexpression also stimulates genome disruption by paired SpCas9n that potentially generate short 3'-overhanging ends at overlapping SpCas9n target sites, suggesting sequential nicking of overlapping target sites by SpCas9n. This approach is further simplified with improved efficiency and safety by fusion of TREX2 and particularly its DNA-binding-deficient mutant to SpCas9n. Junction analysis at overlapping targets revealed the different extent of end resection of 3' single-stranded DNA (ssDNA) by free TREX2 and TREX2 fused to SpCas9n. SpCas9n-TREX2 fusion is more convenient and safer than overexpression of free TREX2 to process 3'-overhanging ends for efficient genome disruption by paired SpCas9n, allowing practical use of this TREX2-based strategy in genome editing.